Design and analysis of a SAW gas sensor based LF RFID tag in 0.18 um CMOS process - Moghavvemi, M.; Attaran, A. (IFSA, 2011)
This paper presents the fully integrated low frequency-radio frequency identification (LF RFID) control logic circuitry for network gas sensing applications. Analog-to-digital-convertor (ADC) interfacing circuitry between RFID and the sensor are analyzed in 0.18 um CMOS process. A highly robust ADC is integrated to ensure the accurate gas detection in the surroundings.